Piknik Bersama Hantu: Alienasi dan Nostalgia dalam Antologi Puisi Perjalanan Menuju Mars karya Irwan Segara - Gregorius Tri Hendrawan Manurung; Laura Andri Retno Martini; Khothibul Umam (Wicara: Jurnal Sastra, Bahasa, dan Budaya, 2024)
This study has material objects in the form of poems "Panggilan dari Malingping", "Kota yang Kehilangan Salak Anjing dan Suara Jangkrik di Jantung Malam" and "Perjalanan Menuju Mars" written by Irwan Segara. This study aims to identify the forms of alienation and nostalgia existing in the three poems and explore relationship between the alienation and nostalgia. Theories applied in this study are Roman Ingarden's theory of norm strata or meaningful layers, Melvin Seeman's theory of alienation, and Svetlana Boym's theory of nostalgia.  The results of this study are as follows: The poems "Panggilan dari Malingping", "Kota yang Kehilangan Salak Anjing dan Suara Jangkrik di Jantung Malam" and “Perjalanan Menuju Mars” present three forms of alienation, namely powerlessness, meaninglessness and self-estrangement. The dominant nostalgic tendency in these three poems is reflective tendency. Nostalgia in these poems were positioned as a response to the alienated condition felt by the subject in these poems, both in the form of escapism and coping.Keywords: poetry, alienation, nostalgia, Irwan Segara